Women in Cuba: The Emancipatory Revolution. (1st April 2016) - Salim Lamrani
Abstract : The triumph of the Cuban Revolution has created the most remarkable political, economic and social upheaval in the history of Latin America. Since its beginning in 1959, the new government, led by Fidel Castro, has placed the poor – especially women and people of colour, the principal victims of the discrimination inherent in patriarchal and segregationist societies – at the centre of their reformist project. The Revolution 'of the humble, by the humble and for the humble', 1 was designed to lay the foundation for a new era, one marked by equality and freed from the throes of the injustice linked to the history and social structures of the country. Cuban women were the immediate priority for the revolutionary government. In 1960, the Federation of Cuban Women (FMC) was created. Its president was Vilma Espín Dubois, the wife of Raúl Castro and a fully committed activist in the struggle against the dictatorship of General Fulgencio Batista. This article examines the status of women at the triumph of the Revolution, and assesses the concrete steps taken to disseminate and implement the idea of equal rights and equal opportunities between men and women and to erase prejudice and cultural stereotypes. Firstly, special attention is paid to the role of women before the triumph of the Revolution. Secondly, the new government's actions aimed at enabling this sector of society to achieve true emancipation and full citizenship are analysed. Finally, beyond the soaring declarations of principle, the article examines the status of Cuban women today and assesses their integration into the political, economic and social life of the country.